Spin Chains with Highly Quantum Character through Strong Covalency in Ca 3 CrN 3 - Kautzsch, Linus; Georgescu, Alexandru B.; Yuan, Lin-Ding; Taddei, Keith M.; Reilly, Aiden; Seshadri, Ram; Rondinelli, James M.; Wilson, Stephen D. (Journal of the American Chemical Society, 2025)
The insulating transition metal nitride Ca CrN consists of sheets of triangular [CrN ] units with symmetry that are connected via quasi-1D zigzag chains. Due to strong covalency between Cr and N, Cr ions are unusually low-spin, and = 1/2. Magnetic susceptibility measurements reveal dominant quasi-1D spin correlations with very large nearest-neighbor antiferromagnetic exchange = 340 K and yet no sign of magnetic order down to = 0.1 K. Density functional theory calculations are used to model the local electronic structure and the magnetic interactions, supporting the low-spin assignment of Cr that is driven by strong π donation from the nitride ligands. The surprising failure of interchain exchange to drive long-range magnetic order is accounted for by the complex connectivity of the spin chain pairs that further frustrates order. Our combined results establish Ca CrN as a nearly ideal manifestation of a quantum spin chain whose dynamics remain unquenched down to extraordinarily low temperatures despite strong near-neighbor exchange coupling.